Merlinda Bobis's fish-hair woman a magical rendering of history - Lye, Kit Ying (Quezon City Ateneo de Manila University, 2017)
"Filipino writers of historical fiction have employed magical realism to incorporate people's experiences into discussions of the nation's violent history and present a possibility of revolution and hope, particularly with the fall of Ferdinand Marcos's regime. However, Merlinda Bobis uses magical realism to represent the struggles of villagers who were caught between government forces and communist insurgents during the Total War in the late 1980s, thus focusing on preserving personal histories and memories. Bobis's Fish-Hair Woman (2012) puts into writing efforts at reconciling with a violent past as she works to actively challenge grander narratives of violence and terror."
Keywords: Philippine literature; Historical fiction; Magical realism; Counterinsurgency